2017
DOI: 10.1177/0260106016688223
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality of individuals with rheumatoid arthritis using the Healthy Eating Index (HEI)-2010

Abstract: The diet quality of many individuals with RA needs improvement and may be related to functional disability associated with RA. Healthcare providers should encourage individuals with RA to meet dietary guidelines and maintain a healthy diet. Moreover, healthcare providers should be aware of the potential impacts of functional disability on diet quality in individuals with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 40 publications
(55 reference statements)
8
46
0
Order By: Relevance
“…Patients with arthritis consumed less fruit, vegetables, greens and beans, whole grains, seafood, and plant protein, but more added sugars, saturated fats, and empty calories compared to those without arthritis [10]. The association of poor dietary quality with RA was also observed in other studies, in which RA patients had an inadequate intake of fruit, vegetables, dairy, fatty acids, and whole grains [11][12][13]. A study in a Chinese population found that RA patients were consuming different amounts of chicken, fish, mushrooms, beans, citrus, dairy products, and organ meats than healthy controls [14].…”
Section: Dietsupporting
confidence: 54%
“…Patients with arthritis consumed less fruit, vegetables, greens and beans, whole grains, seafood, and plant protein, but more added sugars, saturated fats, and empty calories compared to those without arthritis [10]. The association of poor dietary quality with RA was also observed in other studies, in which RA patients had an inadequate intake of fruit, vegetables, dairy, fatty acids, and whole grains [11][12][13]. A study in a Chinese population found that RA patients were consuming different amounts of chicken, fish, mushrooms, beans, citrus, dairy products, and organ meats than healthy controls [14].…”
Section: Dietsupporting
confidence: 54%
“…This study also showed that respondents altered dietary intake of multiple foods together, including gluten, refined sugars, and brewer's yeast. In studies of rheumatoid arthritis, multiple studies have shown a decrease in disease severity or markers of systemic inflammation associated with dietary changes that increase fruit, vegetable, whole grain, and oil intake and reduce or eliminate intake of refined sugars, meat, and animal products [12][13][14][15][16]. These dietary changes are akin to the low glycemic index diet (high in fruits, vegetables and fish, low in carbohydrates), which has been studied for acne as a sole intervention, or paired with metformin, and showed decreases in global acne severity [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of making drastic changes in diet, it is more effective to increase the consumption of fruits, vegetables, grains, and fish and reduce the consumption of meat, refined sugar, white flour, salt and saturated fatty acid [13,14]. In the delay or elimination of chronic inflammation, elimination diet, vegetarianism, and fasting might be effective [4,5,15].…”
Section: Editorialmentioning
confidence: 99%